Formación y trabajo docente: nuevas exigencias profesionales en el mercado educacional - Adolfo Ignacio Calderón; Vlademir Marim (Pontificia Universidad Católica del Perú, 2009)
This article approaches the emergence of a new profile of teachers who work inthe basic education. It debates teachers' education through the light of the analysis of strategies of flexibilization of contractual conditions of teachers who work in the Brazilian private sector, the same ones that demand teachers' educationunder a new commercial paradigm in which the teacher goes from educator to a businessperson and educational entrepreneur. This new paradigm supports the process of expansion of neoliberal policies and thus makes sense in the existing polemics between education as a social right and as merchandise or service. Theauthors verify and discuss the emergence, among the education entrepreneurs, ofrequests for teachers with new professional qualifications, not yet contemplated in the current models of teaching education.